2020
DOI: 10.2147/cmar.s270825
|View full text |Cite
|
Sign up to set email alerts
|

<p>FoxM1 is Upregulated in Osteosarcoma and Inhibition of FoxM1 Decreases Osteosarcoma Cell Proliferation, Migration, and Invasion</p>

Abstract: Background: Osteosarcoma (OS) is a highly aggressive bone malignancy that is mostly diagnosed in children and young adults. Increasing evidence indicates that the transcription factor Forkhead Box M1 (FoxM1) plays a key role in the pathogenesis of various tumors. However, the function of FoxM1 in OS has not been clearly elucidated. Methods: In the present study, we first analyzed the expressions of FoxM1 in human OS and myositis ossificans (MO, included as a control) tissues by immunohistochemistry. To investi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 25 publications
1
5
0
Order By: Relevance
“…Repression of Wnt3a/FOXM1/β-Catenin pathway is widely involved in the apoptotic impact of moracin D in breast cancer [ 39 ]. Consistent with the report of Zhu et al [ 18 ], we verified that FOXM1 was expressed at high levels in OS cells. Further, we investigated the regulation of circ-FOXM1 on FOXM1 and found that circ-FOXM1 could positively regulate FOXM1 mRNA expression at post-transcriptional level but not at transcriptional level.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Repression of Wnt3a/FOXM1/β-Catenin pathway is widely involved in the apoptotic impact of moracin D in breast cancer [ 39 ]. Consistent with the report of Zhu et al [ 18 ], we verified that FOXM1 was expressed at high levels in OS cells. Further, we investigated the regulation of circ-FOXM1 on FOXM1 and found that circ-FOXM1 could positively regulate FOXM1 mRNA expression at post-transcriptional level but not at transcriptional level.…”
Section: Discussionsupporting
confidence: 92%
“…Circ-FOXM1 (hsa_circ_0025033) is a newly recognized cancer-related circRNA located at chr12: 2966846–2983691 and derived from FOXM1 which has been report to be overexpressed in OS and promotes OS progression [ 18 ]. Presently, circ-FOXM1 has been proven to be upregulated in glioblastoma as screened by circRNA microarray [ 19 ].…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have reported finding that FOXM1 functions as an oncogene in the osteosarcoma [ 19 ]. Thus, in order to investigate the potential regulation mediated by FOXD2-AS1, we tried to explore the interaction within FOXD2-AS1 and FOXM1 mRNA.…”
Section: Resultsmentioning
confidence: 99%
“…FOXM1 plays a crucial role in maintaining cell homeostasis by regulating various biological processes, including proliferation, cell cycle progression, differentiation, DNA damage repair, and angiogenesis (5961). FOXM1 is involved in cell entry to both the G1/S and G2/M phases by activating genes regulating these checkpoints (6265). However, our direct comparisons of the TS and Foxm1 KD groups revealed that FOXM1 contributed minimally to the antitumor effects of TS on AtT-20 cells.…”
Section: Discussionmentioning
confidence: 99%